Spiritual Care Intervention on Emotional Regulation in Caregivers with Schizophrenic : A Systematic Review - Maulidiyah Junnatul Azizah Heru; Rizki Fitryasari; Hendy Muagiri Margono (Universitas STRADA Indonesia, 2020)
Schizophrenic client caregivers are faced with various problems caused by the abnormal behavior of schizophrenic clients that can trigger stress. To determine the effectiveness of spiritual care in improving the emotional regulation of caregiver clients with schizophrenia. The sources of the articles used were obtained from searches through the Scopus database Google Scholar, Science Direct, and Proquest. The search for articles is limited from 2015 to 2020. The keywords used are